2015
DOI: 10.5014/ajot.2015.016253
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Falling in People With Chronic Stroke

Abstract: OBJECTIVE. We assessed the prevalence of fear of falling (FoF) in a sample of people with chronic stroke and compared multiple variables (balance, anxiety, depression, activity and participation, and stroke severity) in people with and without FoF. METHOD. This study was a secondary analysis of data collected from a cross-sectional study of mobility after stroke in 77 participants with chronic stroke (>6 mo poststroke). RESULTS. Of the 77 participants, 51 (66%) reported exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 31 publications
6
47
1
Order By: Relevance
“…[35][36][37][38][39] Tsai et al 40) reported fear of falling in almost 70% of community-dwelling stroke survivors, who also had related balance deficits 41) and falls. 40,41) Therefore, to optimize community reintegration, reduction of fear of falling should be a focus in rehabilitation settings. Notably, none of our study subjects stated that they were confident in carrying out all daily activities without falling.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39] Tsai et al 40) reported fear of falling in almost 70% of community-dwelling stroke survivors, who also had related balance deficits 41) and falls. 40,41) Therefore, to optimize community reintegration, reduction of fear of falling should be a focus in rehabilitation settings. Notably, none of our study subjects stated that they were confident in carrying out all daily activities without falling.…”
Section: Discussionmentioning
confidence: 99%
“…As this is the first study to use multivariable analyses to investigate determinants of FOF in persons with late effects of polio, our results are difficult to compare with others. However, in persons with other neurologic diseases, such as stroke and Parkinson disease, decreased balance [33], muscle weakness in the lower limbs [27], and walking limitations [24,34] have been shown to be associated with FOF.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it was the fear of falling that developed immediately after the stroke occurred that predicted falls at follow‐up [17,18]. It has been hypothesized that fear of falling limits patients' mobility, which in turn leads to further deterioration in physical function (balance, strength, and endurance) and leads to falling [19,20]. In addition to its effects on falls, fear of falling is also associated with anxiety [20], poor community reintegration [21], and poor quality of life [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been hypothesized that fear of falling limits patients' mobility, which in turn leads to further deterioration in physical function (balance, strength, and endurance) and leads to falling [19,20]. In addition to its effects on falls, fear of falling is also associated with anxiety [20], poor community reintegration [21], and poor quality of life [22]. Hence, understanding the development of fear of falling after stroke is critical to disrupt the vicious cycle between fear of falling and falls in stroke survivors.…”
Section: Introductionmentioning
confidence: 99%